Factors associated with diarrhea and acute respiratory infection in children under two years of age in rural Bangladesh - Ullah, Md Barkat; Mridha, Malay K.; Arnold, Charles D.; Matias, Susana L.; Khan, Md Showkat A.; Siddiqui, Zakia; Hossain, Mokbul; Paul, Rina Rani; Dewey, Kathryn G. (Springer Link, 2022)
This article was published in The BMC Pediatrics, Springer Link [ © The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s12887-019-1738-6. The Journal's website is at: https://link.springer.com/article/10.1186/s12887-019-1738-6#citeas